A programmed cell division delay preserves genome integrity during natural genetic transformation in Streptococcus pneumoniae. Issue 1 (December 2017) - Bergé, Matthieu; Mercy, Chryslène; Mortier-Barrière, Isabelle; VanNieuwenhze, Michael; Brun, Yves; Grangeasse, Christophe; Polard, Patrice; Campo, Nathalie
Abstract Competence for genetic transformation is a differentiation program during which exogenous DNA is imported into the cell and integrated into the chromosome. InStreptococcus pneumoniae, competence develops transiently and synchronously in all cells during exponential phase, and is accompanied by a pause in growth. Here, we reveal that this pause is linked to the cell cycle. At least two parallel pathways impair peptidoglycan synthesis in competent cells. Single-cell analyses demonstrate that ComM, a membrane protein induced during competence, inhibits both initiation of cell division and final constriction of the cytokinetic ring. Competence also interferes with the activity of the serine/threonine kinase StkP, the central regulator of pneumococcal cell division. We further present evidence that the ComM-mediated delay in division preserves genomic integrity during transformation. We propose that cell division arrest is programmed in competent pneumococcal cells to ensure that transformation is complete before resumption of cell division, to provide this pathogen with the maximum potential for genetic diversity and adaptation. InStreptococcus pneumoniae, competence for genetic transformation is accompanied by a pause in growth. Here, Bergé et al. show that this pause is linked to the cell cycle via at least two pathways that impair peptidoglycan synthesis and preserve genomic integrity during transformation.